El bullying e impacto en el aprendizaje de los estudiantes de 9no de EGBS de la Unidad Educativa Adolfo Valarezo, periodo actual - Jaramillo Cabrera, Darío Xavier (2024)
The present research work focuses on bullying and its impact on the learning of 9th grade EGBS students of the Adolfo Valarezo Educational Unit. Bullying or school harassment is an aggressive, continuous and repetitive behavior that manifests itself in different forms, such as physical, verbal, social or psychological, with the aim of intimidating, humiliating or harming a person. For this reason, the objectives of this research were: “To analyze theoretically and methodologically the types of bullying that are most prevalent among 9th grade students of the Adolfo Valarezo Educational Unit”; “To identify the main causes responsible for the aggressive behavior of 9th grade students of the Adolfo Valarezo Educational Unit” and ‘To design a proposal for social intervention from the point of view of the Social Worker based on mechanisms and protocols of intervention that can be applied in the Adolfo Valarezo Educational Unit, to raise awareness and prevent bullying’, whose purpose is to respond assertively to the problem previously identified. On the other hand, the research method used was inductive, since it facilitated the direct observation of the problem and the identification of an adequate solution. In addition, the research approach was qualitative, which made it possible to analyze and characterize the processes before and after the intervention. By means of the results obtained through the application of the different research and evaluation instruments, the following significant results could be evidenced; 38.46% of the students have witnessed bullying in the institution and 34.62% have been victims of bullying in the educational institution, it is necessary to consider that these results show that more than a third of the students have been victims or witnesses of this phenomenon, which is essential that the competent authorities take measures to prevent and eradicate bullying. In conclusion, this research project highlights the importance of addressing the problem of bullying in a comprehensive manner, involving all actors in the educational community and it is necessary to continue researching and developing innovative strategies to eradicate bullying and ensure the welfare of all students, since a significant proportion of them have been victims or witnesses of bullying. It is imperative that school authorities implement the recommendations derived from this study to effectively combat bullying.